Implementasi Undang-Undang Nomor 3 Tahun 2002 tentang Pertahanan Negara dalam Menghadapi Gangguan Militer (Jurnal Begawan Hukum (JBH), 2025)
Law Number 3 of 2002 concerning National Defense states that the General Policy on National Defense functions as a guideline for the management, implementation and supervision of national defense. The aim of this study is to show that the various players participating in state practices require organizing the implementation of national security through integrated mechanisms that consider all factors to produce the best results. To create national security, it is necessary to combine the capabilities of the entire country, including security forces, law enforcement, government agencies and the entire community. In qualitative research, data is collected methodically, factually and quickly using descriptive methodology according to the description at the time of the research. The findings of this research show that the TNI's task is to fight all military and armed disturbances, both domestically and internationally. Therefore, the TNI is also tasked with dealing with deviant beliefs and other armed conflicts that occur in Indonesia, such as what happened in Papua.